Correlation between Total Monocyte, Lymphocyte and Basophil Counts, as well as Monocyte-Lymphocyte Ratio with Hematocrit as Indicators of Plasma Leakage in Dengue Virus Infection - Jamiko, Safari Wahyu; Yulistina, Desita; Ardhana, Regita; Puspitasari, Metana (Universitas Muhammadiyah Surakarta, 2024)
Background: Severe dengue virus (DVI) infection is characterized by plasma leakage (PL) due to the release of vasoactive cytokines by immunocytes such as monocytes, lymphocytes, and basophils. The response to Dengue Virus (DENV) also affects the kinetics of monocytes, lymphocytes, and basophils, thus changing the examination results of leukocyte types and monocyte-lymphocyte ratio (MLR). MLR has been used as a biomarker and outcome predictor in various diseases but not to predict PL in DVI. Objectives: To see the correlation of monocytes, lymphocytes, basophils, and MLR with hematocrit (Hct) which is a PL indicator. Methods: Correlative analytical research with a cross-sectional approach was conducted on 71 pediatric DVI patients at PKU Muhammadiyah Sampangan Hospital, Surakarta, in February- April 2024. The diagnosis of DVI was confirmed by a pediatrician according to WHO 2009 criteria. DVI patients who had a history of allergies, worms, malignancies, and DVI with secondary infections were excluded from the study. Absolute monocyte (AMC), lymphocyte (ALC), and basophil (ABC) count values ​​, as well as MLR and Hct, were obtained from the results of a complete blood examination using a hematology analyzer. The Spearman Rho’s correlation test was used to determine the relationship between variables with values ​​of p<0.05 and r>0.4 considered significant. Results: research obtained AMC=median 313 (IQR 192) mm-3, ALC= median 1225 (IQR 1039) mm-3, ABC=0 mm-3, MLR=0.22 (0.23). The results of the correlation analysis of AMC, ALC, and MLR with Hct are AMC (r=0.01, p=0.918), ALC (r=0.351, p=0.003), and MLR (r=0.41, p<0.001), while the correlation between ABC and Hct could not be done due to no data variation. Conclusion: There is a significant correlation between MLR and Hct, but not with AMC, ALC, and ABC and Hct. MLR can potentially predict plasma leakage in patients with dengue virus infection.